The Effectiveness of Learning with Brain in mind in Achievement at Elementary _ Fourth Class students in Science An experimental study in Damascus - Hamdan, Rwaida; Khansa, Abeer (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aimed at recognizing the efficiency of learning with brain in mind in the achievement of basic fourth- grade students in science, this study was adopted on experimental approach. The research tool formed of Quasi-experimental program designed according to Learning with brain in mind by the researcher, and achievement test. The population of the research consisted of (177854) fourth- grade basic education students in Damascus. The research sample consisted of (72) male and female students divided into two groups: an experimental group consisted of (34) male and female students of Safia Al-qurashia school studied by Learning with brain in mind strategy, and a control group consisted of (38) male and female students of the same school studied by traditional manner. The findings of the study were as follows: - The Learning with brain in mind was effective in the improvement of achievement of basic fourth grade students in science. - There were significant statistical differences between the mean scores of students in the experimental group for the pre and post of achievement test. - There were significant statistical differences between the mean scores of students of the experimental group and the control group in the post to achievement test. Similar studies are suggested for different age stages and studying subjects.